Respuesta :

Answer:

a ) y = 1 and x = -1

d) y = 5 and x = -1/2

Step-by-step explanation:

Substitution method

Question a

y = x+ 2

y = 2x + 3

we can make the first formula in terms of x , so we can place in into the second formula

y = x + 2

x = y -  2

now put y - 2 where x is in the second equation

y = 2x + 3

y = 2(y - 2) + 3

y = 2y - 4 +3

now solve

4 - 3 = 2y -y

y = 1

since y = 1 we can find what x is by putting into the first formula

y = x +2

x = y - 2

x = (1) -2

x = -1

hence y = 1 and x = -1

Question d

y = 2x + 6

y = 4 - 2x

we can make the first formula in terms of x , so we can place in into the second formula

y = 2x + 6

y - 6 = 2x

x = (y-6)/ 2

now place (y-6)/2 where x is in the second formula

y = 4 -2x

y = 4 - 2 ([tex]\frac{y - 6}{2}[/tex])

now solve

the multiplication by 2 and division by 2 are cancelled out

hence making the simplified equation as:

y = 4 - y + 6

2y = 4 + 6

2y = 10

y = 5

now place this into the first equation

y = 2x + 6

y - 6 = 2x

x = (y-6)/ 2

x = (5-6)/2

x = -1/2

hence y = 5 and x = -1/2

ACCESS MORE